2003
DOI: 10.1093/brain/awg090
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the tau gene that cause an increase in three repeat tau and frontotemporal dementia

Abstract: The majority of cases with frontotemporal dementia (FTD) have no tau deposition in the brain, yet mutations in the tau gene lead to a similar clinical phenotype with insoluble tau depositing in neuropathological lesions. We report two tau gene mutations at positions +19 and +29, in the intronic sequences immediately following the stem loop structure in exon 10, which segregate with FTD. Exon-trapping experiments showed that these gene mutations alter the splicing out of exon 10 and produce an increase in tau i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 45 publications
1
102
0
Order By: Relevance
“…In this report we investigate the mechanism of action of SR protein 9G8, which inhibits inclusion of exon 10 ). Our results show that 9G8 directly interacts with the proximal downstream intron of exon 10, a clustering region for FTDP mutations (D 'Souza et al, 1999;Hutton et al, 1998;Stanford et al, 2003).…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…In this report we investigate the mechanism of action of SR protein 9G8, which inhibits inclusion of exon 10 ). Our results show that 9G8 directly interacts with the proximal downstream intron of exon 10, a clustering region for FTDP mutations (D 'Souza et al, 1999;Hutton et al, 1998;Stanford et al, 2003).…”
Section: Introductionmentioning
confidence: 59%
“…Exon 10 splicing is affected by exonic and intronic enhancers and silencers (D 'Souza et al, 1999;Schellenberg, 2000 D'Souza andSchellenberg, 2002;Gao et al, 2000;Grover et al, 1999;Hutton et al, 1998;Stanford et al, 2003;Wang et al, 2004), as well as by several trans factors and their phosphorylation (Broderick et al, 2004;Gao et al, 2000;Hartmann et al, 2001;Jiang et al, 2003;Kondo et al, 2004;Wang et al, 2004Wang et al, , 2005. Two regulatory elements and the factors that regulate them have been characterized within exon 10: an AT rich silencer that binds SRp30c and SRp55 which inhibit inclusion of exon 10 (Wang et al, 2005) and a purine-rich enhancer directly downstream of the silencer that binds htra2beta1 which activates inclusion of exon 10 (Jiang et al, 2003;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several TAU mutations are genetically linked to fronto-temporal dementia (FTD). [5][6][7][8][9][10][11][12] Tau expression is regulated by alternative splicing in a speciesspecific, developmental-and tissue-dependent manner. [13][14][15][16] Depending upon the inclusion or exclusion of exon 10, Tau isoforms with three or four microtubule binding domains are generated (3R and 4R, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…In cases of frontotemporal dementia, an increase in tau degradation was observed that was histologically associated with DNA fragmentation and caspase 3 activation in neurons [208]. Taken together with the biochemical data for the caspase processing of tau, these results suggest that tau cleavage may be a significant contributory factor in the pathogenesis of Alzheimer's disease.…”
Section: Multiple Pathways For Caspase Activity To Influence the Toximentioning
confidence: 61%